On the Zeros of a Class of Polynomials and Related Analytic Functions (Analysis in Theory and Applications, 2012)
In this paper we prove some interesting extensions and generalizations of Enestrom-Kakeya Theorem concerning the location of the zeros of a polynomial in a complex plane. We also obtain some zero-free regions for a class of related analytic functions. Our results not only contain some known results as a special case but also a variety of interesting results can be deduced in a unified way by various choices of the parameters.